(untitled) (Bangladesh Journal of Microbiology, 2010)
Black quarter (BQ) is an acute, infectious disease caused by Clostridium chauvoei - a Gram-positive, anaerobic organism. This disease is characterized by inflammation with gaseous oedema of skeletal muscle and severe toxaemia. This study was done in Upazilla Veterinary Hospital at Raozan in Chittagong from June to August 2006. During the study period, 25 cases of BQ in cattle were found in eight Unions. Among them the highest (32%) proportion of BQ was found in Raozan Union. Frequency of BQ according to demographic variable was: age incidence of >12 month (60%), male (60%), breed of Red Chittagong (44%), body condition score (BCS) of BCS-2 (88%), and affected body part involving hind quarter muscle (35%). Death was observed with 73% cases. In case of animals that were suffered from BQ, septicaemia developed after 12 h of onset of clinical signs and symptoms. Treatment was ineffective in advanced septicaemic stage. Antibiotic therapy was found to be effective when administered within 12 h of the clinical symptoms. Keywords: Black quarter; Clostridium chauvoei; Demographic variable; Septicaemia; Antibiotic therapy DOI: http://dx.doi.org/10.3329/bjm.v25i1.4848 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 13-16